Hubungan Tingkat Pengetahuan Terhadap Manajemen Diri Pasien Prolanis Diabetes Mellitus Tipe 2 di Puskesmas 1 Purwokerto Timur - Nurasyifa, Siti Rohimah; RU, Vitis Vini Fera; Pratiwi, Hening (Acta Pharmaciae Indonesia, 2021)
Diabetes mellitus is a disease characterized by blood glucose elevation and long-term illness that requires good self-management. Patient knowledge has important role to overcome self-management. This study aims to assess relationship between patient's knowledge level and self-management. This research used observational study with cross sectional approach. Patient knowledge level was measured by Diabetes Knowledge Questionnaire (DKQ-24) and self-management level was measured by Diabetes Self-Management Questionnaire (DSMQ). This study was held in East Purwokerto I Public Health Center and data sources were collected by accidental sampling technique. The sample used in this study was 35. The result showed that there was a correlation between patient knowledge level to self-management p = 0,000, r = 0,838 in diabetes mellitus type 2.